2013
DOI: 10.1111/bjd.12567
|View full text |Cite
|
Sign up to set email alerts
|

First left-right comparative study of topical rapamycin vs. vehicle for facial angiofibromas in patients with tuberous sclerosis complex

Abstract: SummaryBackground Tuberous sclerosis complex (TSC) is an autosomal dominant disorder causing multiple hamartomas. Treatment of TSC lesions with mammalian target of rapamycin inhibitors is effective. Recently, several reports have shown the efficacy of topical rapamycin (sirolimus) for angiofibromas. However, almost all studies have been case studies and the 0Á1% solution caused skin irritation. A comparative study of topical rapamycin and a vehicle has not yet been reported. Objectives To compare the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 16 publications
6
64
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13] The articles were limited to those available in the English language and they were read, and any relevant articles referred to in the references were also included in the study. Of these, 11 were case series and one was a review article.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] The articles were limited to those available in the English language and they were read, and any relevant articles referred to in the references were also included in the study. Of these, 11 were case series and one was a review article.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus and everolimus, two immunosuppressant compounds that inhibit mTOR (12)(13)(14), are effective in decreasing the size of renal angiomyolipomas in patients with TSC or LAM (15)(16)(17), and reducing the size of giant cell astrocytomas and the severity of skin angiofibromas in patients with TSC (18)(19)(20). Treatment with sirolimus for 1 year decreased the rates of decline in FVC and FEV 1 and improved quality of life (21).…”
mentioning
confidence: 99%
“…Several studies have reported that sirolimus plasmatic concentration remains undetectable even in daily application (3,5,6,10,11). These determinations were not made in our patients.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 68%
“…On one hand the average age of our series (40,25) was older than the reviewed in the literature [16 (3), 17,9 (4), 21,77 (5), 20,5 (6), 8,5 (7), 13,5 (8), 17,6 (11), 11 (12), 27 (13), 10,6 (14)]. In fact it is supposed that the younger patients have an earlier and greater response to topical rapamycin (4,7,11,15). It is possible that FA in children and teenagers are less fibrotic than those of older patients in which fibrosis is established.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%